CT Features of COVID-19 Pneumonia Differ Depending on the Severity and Duration of Disease - Schaible, Jan; Meiler, Stefanie; Poschenrieder, Florian; Scharf, Gregor; Zeman, Florian; Knobloch, Charlotte; Rennert, Janine; Pregler, Benedikt; Kleine, Henning; Menzel, Cynthia; Stroszczynski, Christian; Zorger, Niels; Hamer, Okka W (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Background CT is important in the care of patients with COVID-19 pneumonia. However, CT morphology can change significantly over the course of the disease. To evaluate the CT morphology of RT-PCR-proven COVID-19 pneumonia in a German cohort with special emphasis on identification of potential differences of CT features depending on duration and severity of disease.Method All patients with RT-PCR-proven COVID-19 pneumonia and chest CT performed between March 1 and April 15, 2020 were retrospectively identified. The CT scans were evaluated regarding the presence of different CT features (e. g. ground glass opacity, consolidation, crazy paving, vessel enlargement, shape, and margin of opacifications), distribution of lesions in the lung and extent of parenchymal involvement. For subgroup analyses the patients were divided according to the percentage of parenchymal opacification (0–33 %, 34–66 %, 67–100 %) and according to time interval between symptom onset and CT date (0–5 d, 6–10 d, 11–15 d, > 15 d). Differences in CT features and distribution between subgroups were tested using the Mantel-Haenszel Chi Squared for trend.Results The frequency of CT features (ground glass opacity, consolidation, crazy paving, bronchial dilatation, vessel enlargement, lymphadenopathy, pleural effusion) as well as pattern of parenchymal involvement differed significantly depending on the duration of disease and extent of parenchymal involvement. The early phase of disease was characterized by GGO and to a lesser extent consolidation. The opacifications tended to be round and to some extent with sharp margins and a geographic configuration. The vessels within/around the opacifications were frequently dilated. Later on, the frequency of consolidation and especially crazy paving increased, and the round/geographic shape faded. After day 15, bronchial dilatation occurred, and lymphadenopathy and pleural effusion were seen more frequently than before.Conclusion The prevalence of CT features varied considerably during the course of disease and depending on the severity of parenchymal involvement. Radiologists should take into account the time interval between symptom onset and date of CT and the severity of disease when discussing the likelihood of COVID-19 pneumonia based on CT morphology.Key Points: Citation Format
Keywords: COVID-19 pneumonia; CT; morphology; severity; duration